Mutational Characteristics of Causative Genes in Chinese Hereditary Spherocytosis Patients: a Report on Fourteen Cases and a Review of the Literature - Wang, Dong; Song, Li; Shen, Li; Zhang, Kaihui; Lv, Yuqiang; Gao, Min; Ma, Jian; Wan, Ya; Gai, Zhongtao; Liu, Yi (Frontiers in Pharmacology, 2021)
Background Hereditary spherocytosis (HS), characterized by the presence of spherocytic red cells in peripheral blood, hemolysis, splenomegaly, jaundice, and gallstones, is a common form of inherited hemolytic anemia (HA). To date, five causative genes associated with HS have been identified, including ANK1, SPTB, SPTA1, SLC4A1, and EPB42. Methods The clinically suspected patients with HS or undiagnosed HA from 14 Chinese families were enrolled in this study. We presented the patients’ clinical features and identified the causative gene variants in these patients using whole exome sequencing (WES), with 10 novel and 4 reported mutations in ANK1 and SPTB genes (7 mutations in ANK1 and 7 in SPTB), individually. Then, we reviewed all available literatures of Chinese HS patients from 2000 to 2020 in PubMed and Chinese Journals with genetic results and clinical information, so as to delineate gene mutation spectrum and potential correlation with phenotypes. Results Total 144 variants have been reported in 144 different Chinese families. These reports combining with our data indicated that ANK1 (46%) and SPTB (42%) were the most frequently mutated genes in Chinese HS patients, followed by SLC4A1 (11%) and SPTA1 (1%), while no mutations in EPB42 was reported. Most of mutations in ANK1 and SPTB were nonsense (26/73 in ANK1 and 32/66 in SPTB) and frameshift (20/73 in ANK1 and 15/66 in SPTB), while missense mutations (14/18) account for the majority in SLC4A1. The higher mutation frequency of ANK1 was found in its exon 8, 9, 26 and 28; the majority of mutations in SPTB were located in its exon 13, 15, and 18 to 30; whereas mutations in SLC4A1 were scattered throughout entire region of the gene. Conclusion The mutation spectrum of HS was further expanded due to the identification of the mutations in this study indicating that WES is an effective and accurate diagnostic tool for discovering causative gene mutations for HS. Moreover, for the first time, a review of literature is conducted to clarify the mutational characteristics of causative genes reported in Chinese HS patients.